The Effect of Stock Speculation on the New York Money Market - Rogers, James Harvey (Quarterly Journal of Economics, 1926)
Plan of investigation, 435. — Amount of deposit currency used in stock-exchange speculation, 436. — Computation of its velocity of circulation, 439. — Restatement of results of the investigation of velocity of circulation of brokers' deposits, 444. — The amount and importance of bank loans used, 446. — Significance of the great increase in street loans during the summer and fall of 1925, 450. — Analysis of the problem of the increase in brokers' loans amplified, 451. — The effect of the expansion of street loans on the further loaning capacity of the American banking system as a whole, 452. — Certain implications of the conclusions arrived at, 455.